KINDS OF SPEECH ACT USED TO TEACH SPEAKING FOR GRADE 11 STUDENTS: AN ANALYSIS STUDY - Reza Agnes Sindy Lorensa; Muh Shofiyuddin (IKIP Siliwangi, 2024)
Speech acts are utterances that contain an intention towards the listener. Speech acts are intended to convey information, ideas or thoughts from someone. The aim of this study is to find out the kind and dominant speech acts used to teach speaking to students by English teachers during learning activities. The researchers used speaking materials for their analysis. The method used in this study is a qualitative descriptive method. The results of this analysis show that there are 123 utterances or speech acts that can be classified. The data that has been obtained can be directly classified into 3 types of speech acts, the name is Locutionary, Illocutionary, and Perlocutionary. It is very important to understand the meaning of utterences in English. This is to avoid misunderstandings in the meaning of speech.